P4PABI : Philosophy for persons with acquired brain injuries - Backman, Ylva; Gardelli, Teodor; Gardelli, Viktor; Gardelli, Åsa; Strömberg, Caroline (Luleå tekniska universitet, Pedagogik, språk och Ämnesdidaktik, 2012)
Aim The aim of this study is to examine to what extent philosophical dialogue can be a good tool for persons with acquired brain injuries (ABI) to regain lost abilities and develop new capabilities that are relevant for participating in the society. Methodological framework The empirical data has been collected during nearly two years of philosophical practice with students at the Brain injury program at Framnäs folk high school in northern Sweden. All students at the program have ABI. Persons with ABI may have lost their ability to take positions and they often have difficulties to give arguments and to express themselves clearly. The students that participated in this study have had an ABI and are left with such severe residual functional capacity that their lives have totally changed. The philosophical practice has been inspired by basic ideas from philosophy with children. It is important that individuals with disabilities are viewed as experts in their own recovery process, where their feelings and experiences are treated as valuable in guiding subsequent rehabilitation decisions. Both students and staff have been provided the opportunity to make their voice heard during this project. Hereby, we have approached the experienced utility of philosophical dialogues for persons with ABI from three perspectives; that of the students, the staff and us as participating researchers in the project group. Conclusions In general, the preliminary results indicate that the philosophical practice with the students with ABI has been positive for the students to regain lost abilities and develop new capabilities relevant for participating in society. Relevance to Nordic educational research In Sweden, research on philosophical practice is still highly infrequent, which makes research on philosophical dialogue in educational institutions that are special and typical for Sweden very important. However, research on philosophical dialogue with persons with ABI is very rare - to our knowledge, non-existing, apart from our study ...